Microbial rhizosphere communities in response to chlorimuron-ethyl herbicide in soils under alfafa crop - Ding, Junnan; Li, Xin (Sociedade Brasileira de Ciência do Solo, 2022)
Biolog Eco technology was used to investigate the effects of different chemical herbicide application methods, such as pre-emergence after sowing and post-emergence (stem and leaf spraying), on the characteristics of carbon source utilization by microbial communities in alfalfa rhizosphere soil. The averages of well color development (AWCD) and microbial metabolism diversity indices of post-emergence herbicide spraying on stems and leaves were significantly lower than those of pre-emergence herbicide and without herbicide treatments. Furthermore, pre-emergence after sowing herbicide treatment did not affect soil microorganisms. The principal component analysis (PCA) revealed that the microbial community diversities of the rhizosphere soils differed significantly between herbicide treatments. Carbohydrate was the carbon source type that was most sensitive to herbicide treatment changes, followed by amino acids and carboxylic acids. The herbicide application method significantly reduced the capacities of the microbial community to utilize the carbon sources, as mainly manifested in the ability to use polymers. As shown by a comprehensive analysis on the growth of alfalfa and the physiological and biochemical indices of its root system, the application of herbicide chlorimuron-ethyl reduced the alfalfa yield, and the two different application methods tested showed no significant difference. Herbicide application and different application methods showed significant impacts on alfalfa root activity and membrane permeability, suggesting that the application of herbicide damaged the membrane permeability and the activity of the alfalfa root system. Impacts of herbicide residues in the soil after stem and leaf post-emergence treatment on alfalfa growth and soil microorganisms should not be ignored.
Keywords: herbicide; biologic; soil microbial community; AWCD; PCA